The Effect of Using Google Translate as a Machine Translation on the Writing of Student’s at the University - Syahadah; Repelita Waty Br Kembaren, Farida (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This study aims to examine the effect of using Google Translate as a machine translation students writings at the State Islamic University of North Sumatra (UINSU) Medan. The research method used in this study is a qualitative approach, and the research design used descriptive analysis. The data collection technique in this study used questionnaires and interviews, which were distributed to participants where a total of 20 questionnaires were answered based on their own opinions and reinforced with interview results. Participants in this study involved 10 English education students who used Google Translate (GT) as machine translation in translating their academic assignments. The result of this study is that GT has a significant impact on the grammatical accuracy and the quality of sentence structure in students' writing. However, this tool has a more pronounced strength in handling simple sentences compared to complex sentences. Although it is capable of providing a fairly helpful initial translation, the results still require manual review and additional editing to produce writing that is more natural and truly adheres to English grammar rules.